2011
DOI: 10.1007/s00296-011-2239-6
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of Rituximab in refractory pediatric systemic lupus erythematosus nephritis: a single-center experience of Northern Greece

Abstract: Lupus nephritis (LN) is the major determinant of outcome in pediatric systemic lupus erythematosus (pSLE), and its treatment remains a challenge. The aim of this study was to report the experience of our center in treating with rituximab (RTX) SLE patients with severe LN. Four pSLE patients with biopsy-proven LN, who are refractory to conventional immunosuppressive treatment, received four doses of 375-500 mg/m(2) RTX, 2-3 weeks apart. All patients were concurrently receiving corticosteroids (CSs) and mycophen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 25 publications
0
4
0
3
Order By: Relevance
“…Two clinical trials with rituximab in patients with lupus have not confirmed the efficacy suggested by case-series and recent cohort studies [6][7][8][9][10][11][12]. In the EXPLORER trial that included patients with moderately-to-severely active systemic lupus erythematosus, no differences in the proportion of patients achieving and maintaining a partial or complete response were found between rituximab and placebo [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two clinical trials with rituximab in patients with lupus have not confirmed the efficacy suggested by case-series and recent cohort studies [6][7][8][9][10][11][12]. In the EXPLORER trial that included patients with moderately-to-severely active systemic lupus erythematosus, no differences in the proportion of patients achieving and maintaining a partial or complete response were found between rituximab and placebo [25].…”
Section: Discussionmentioning
confidence: 99%
“…Although several authors have analyzed the off-label use of rituximab in patients with specific diseases, mainly systemic lupus erythematosus, lupus nephritis and other severe refractory systemic autoimmune diseases [6][7][8][9][10][11][12], data on its use in different off-label indications are scarce [13][14][15]. The aim of this study was to analyze the indications for off-label use of rituximab in our centres, the available evidence when it was used, the outcomes of treated patients, as well as the cost.…”
Section: Introductionmentioning
confidence: 99%
“…Although only 15-20% of cases are diagnosed in childhood, SLE has a more severe phenotype in children compared to adults, particularly in those with nonwhite ethnicity 7,8,9 . Several open-label studies of RTX in pediatric subjects have demonstrated benefit in life-threatening or organ-threatening SLE 5,10,11,12,13,14,15 . However, limitations of these studies include low patient numbers and demographic cohorts not representative of many patients with SLE in the United States.…”
mentioning
confidence: 99%
“…Вопрос применения ритуксимаба в схемах терапии СКВ остается открытым. С одной стороны, в единичных слу-чаях, а также при анализе серии клинических наблю-дений показана эффективность препарата у пациентов с очень высокой активностью СКВ, резистентных к пред-шествующей терапии и высоким риском летального исхода [38][39][40]. С другой стороны, в немногочисленных ретроспективных исследованиях нет указаний на суще-ственное превосходство схем с применением ритукси-маба по отношению к схемам лечения без него [41,42].…”
Section: обмен опытомunclassified